Co-management brings hope for effective biodiversity conservation and socio-economic development in Vwaza Marsh Wildlife Reserve in Malawi - Manda, Leonard; Salako, Kolawolé Valère; Kataya, Andrew; Affossogbe, Sèdjro A. T.; Njera, Dalo; Mgoola, William O.; Assogbadjo, Achille Ephrem; Sinsin, Brice (Frontiers in Conservation Science, 2023)
Co-management has been widely promoted in protected area management on the premise that it may simultaneously enhance biodiversity conservation outcomes and improve the livelihoods of the park-border communities. However, the success of this management approach remains a growing debate raising the question of its effectiveness. To contribute to this debate, we used local community perceptions and secondary ecological data to assess the extent to which co-management has effectively contributed to biodiversity conservation in the Vwaza Marsh Wildlife Reserve. Face-to-face individual interviews using a semi-structured questionnaire were used to collect data on the perceptions of co-management from 160 purposively selected heads of households. A desk study was used to collect data on trends in animal populations, animal mortality, and prohibited activities, covering a period of the past 30 years (pre-and post-introduction of co-management). Results showed that local communities have positive perceptions of the conservation work in the Vwaza Marsh Wildlife Reserve, thus partly demonstrating the success of co-management in the area. Further, there was an improved people-park relationship and a recovery of animal populations in the reserve after the introduction of co-management. However, misunderstandings over revenue sharing were still a thorny issue, somehow creating mistrust between parties. We concluded that while it may still be early to achieve more demonstrable conservation outcomes, co-management appears to bring hope for biodiversity conservation in the Vwaza Marsh Wildlife Reserve. Moving forward, participatory evaluation of co-management involving key stakeholders is recommended in the Vwaza Marsh Wildlife Reserve based on the findings of this study and lessons learnt over the years.